2000
DOI: 10.1016/s0006-3495(00)76853-6
|View full text |Cite
|
Sign up to set email alerts
|

Buffer Effects on Electric Signals of Light-Excited Bacteriorhodopsin

Abstract: Buffers change the electric signals of light-excited bacteriorhodopsin molecules in purple membrane if their concentration and the pH of the low-salt solution are properly selected. "Positive" buffers produce a positive component, and "negative" buffers a negative component in addition to the signals due to proton pumping. Measurement of the buffer effects in the presence of glycyl-glycine or bis-tris propane revealed an increase of approximately 2 and a change of sign and a decrease to approximately -0.5 in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 31 publications
1
13
0
Order By: Relevance
“…It has been demonstrated earlier that the opposite process ( i.e. proton release to the bulk in the normal photocycle) is accompanied by a conformational change in the PRG (42). Based on this, and the similar kinetics of the signals in Fig.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…It has been demonstrated earlier that the opposite process ( i.e. proton release to the bulk in the normal photocycle) is accompanied by a conformational change in the PRG (42). Based on this, and the similar kinetics of the signals in Fig.…”
Section: Resultsmentioning
confidence: 97%
“…We found earlier that PERS of light‐excited BR measured with and without GG buffer differ in the microsecond time range (42–44). Shortly, the difference between these signals showed that they originated from the protons that were released at the extracellular surface by the PRG and moved on the buffer gradient (42). This “buffer signal” reflects the appearance of protons in solution, consequently we consider it as a differential response of proton release ( i.e.…”
Section: Resultsmentioning
confidence: 97%
“…On the contrary, the ''buffer effect'' responds to the protons as released. The protein electric response signals (PERS) of light excited BR measured with and without GG differ in the microsecond time range (6,7,16,17). Detailed study of the difference between these signals showed that they originated from the protons that were released at the extracellular surface by PRG and moved on the buffer gradient (6).…”
Section: Methodsmentioning
confidence: 99%
“…The buffer signal has rising and decaying components with lifetimes of ;50 and 250 ms. The interpretation of these two components is given in Tóth-Boconádi et al (6). Shortly, protons move from the Schiff-base to Asp-85 during L/M transition; the change of electric field rearranges the proton release group (rise of buffer signal), which then releases the proton (decay of buffer signal).…”
Section: Measurements With Indicator Dyementioning
confidence: 99%
See 1 more Smart Citation